Pengelolaan Agrowisata Berbasis Swasembada. Studi Kasus Program Kampoeng Tematik Jamrut Di Desa Mendak, Kecamatan Gunung Pati - Rohmah, Fidiatur; Nisa, Luthfia Khoirun; Najwa, Nazalatun; Amanda, Winda; Safira, Tria (CV.ITTC INDONESIA, 2025)
Kampoeng Thematic Jamrut, Mendak Village, Gunung Pati District is one of the results of the Thematic Village planning innovation formed in 2016 by the Semarang City government. The people of Mendak Village have succeeded in realizing a village with the name of agro-tourism. With an area of about 8,000 square meters, the people of Mendak Village are able to manage the land as agricultural land for various types of fruits. This research was conducted to find out how the management carried out in Kampoeng Thematic Jamrut from the beginning of the formation to the formation of a village called agrotourism. The research methods used are qualitative research methods and data collection techniques in the form of observations, interviews, and documentation studies. The primary data source was obtained from the head of the RT as well as the head of the village farmer which was directly collected by the researcher as the main source of support for this research. The results of the study show that the Kampoeng Jamrut Thematic agrotourism in Mendak Village is able to generate awards at various events and is able to bring change in the village, including in terms of the economy. Agro-tourism management is carried out jointly by the community by involving the role of the government as the initial facilitator of the formation to show development in rural areas.